Prevention and Management of Complications of and Training for Colorectal Endoscopic Submucosal Dissection - Naohisa Yoshida; Nobuaki Yagi; Yutaka Inada; Munehiro Kugai; Akio Yanagisawa; Yuji Naito (Gastroenterology Research and Practice)
Endoscopic submucosal dissection (ESD) is reported to be an efficient treatment with a high rate of en bloc resection for large colorectal tumors in Japan and some other Western and Asian countries. ESD is considered less invasive than laparoscopic colectomy. However, ESD carries a higher risk of perforation than endoscopic mucosal resection (EMR). Various devices and training methods for colorectal ESD have been developed to solve the difficulties. In this review, we describe the complications of colorectal ESD and prevention of those complications. On the other hand, colorectal ESD is difficult for less-experienced endoscopists. The unique step-by-step ESD training system is performed in Japan. Additionally, appropriate training, including animal model training, for colorectal ESD should be acquired before working on clinical cases.